Clinical and Ophthalmological Characteristics of Ocular Syphilis in a Retrospective Tertiary Hospital Cohort. Issue 6 (June 2021) - Wagner, Laura F.; Lanzl, Ines; Rothe, Kathrin; Schneider, Jochen; Zink, Alexander; Zapp, Daniel; Schwerdtfeger, Christiane; Lee, Marcel; Weidlich, Simon; Neuenhahn, Michael; Loos, Daria; Spinner, Christoph D.
Abstract : Background: Data on ocular syphilis (OS) and its clinical presentation are currently insufficient. This study aimed to investigate the characteristics of a cohort with a high OS incidence at a university hospital in Germany, focusing on the clinical presentation of OS. Methods: This single-center cohort study retrospectively analyzed data on 90 patients with 109 episodes of syphilis between 2008 and 2018. Cases of OS were identified and additionally reevaluated through a study-specific secondary assessment by an ophthalmologist specializing in uveitis. Results: Twenty-three patients (26%) were diagnosed with OS, 16 (70%) of whom were with binocular involvement. Uveitis, especially that of the posterior segment, showed a high prevalence. Lumbar puncture was performed in 20 OS patients (87%), of whom 17 (85% of those with lumbar puncture/74% in total) met the 2018 Centers for Disease Control and Prevention criteria for likely neurosyphilis. Five (22%) of 23 patients had HIV infection, of whom 2 did not receive antiretroviral therapy. The preferred syphilis treatment regimens were benzylpenicillin and ceftriaxone, which yielded favorable serological, clinical, and ophthalmological outcomes. Conclusions: A high incidence of OS was identified, and physicians should be aware of uveitis as a manifestation of syphilis. Most patients presented with uveitis and syphilis in an early or late latent stage and showed central nervous system involvement. Abstract : A retrospective study of patients with syphilis at a tertiary university hospital in Germany found a high incidence of ocular syphilis and active neurosyphilis between 2008 and 2018.